A novel Nb superconducting joint with ultralow resistance fabricated by electron beam welding method for superconducting gravimeter. (3rd December 2021) - Zhang, Zili; Huang, Xing; Cui, Chunyan; Wang, Hao; Niu, Feifei; Zhang, Yuan; Kong, Xiangdong; Han, Li; Wang, Lei; Hu, Xinning; Wang, Qiuliang
Abstract: This paper presents a novel Nb superconducting joint with an ultralow resistance of 7.9 × 10 −16 Ω, fabricated using the electron beam welding (EBW) method. After the EBW process, the two Nb filaments formed a single joint with a much larger grain size and smaller grain misorientation. More importantly, the resistance of the EBW Nb joint was nearly one magnitude lower than that of most conventional pressing joint. The ultralow resistance is essential for superconducting gravimeters, which require an extremely low drift rate. The EBW Nb joint allowed the superconducting gravimeter to have a much better performance when applied in the field of structural geology, geodesy, microgravity, and metrology. We believe that the EBW method could be one of the most promising joint fabrication methods for achieving maximum stability (less than 1 μ gal yr −1 ).